To solve the quadratic equation \(2x^2 - 5x = 6\), we first rearrange it to the standard form:
\[ 2x^2 - 5x - 6 = 0 \]
Next, we can use the quadratic formula:
\[ x = \frac{-b \pm \sqrt{b^2 - 4ac}}{2a} \]
Here, \(a = 2\), \(b = -5\), and \(c = -6\).
-
Calculate the discriminant: \[ b^2 - 4ac = (-5)^2 - 4(2)(-6) = 25 + 48 = 73 \]
-
Now apply the quadratic formula: \[ x = \frac{-(-5) \pm \sqrt{73}}{2(2)} = \frac{5 \pm \sqrt{73}}{4} \]
-
Calculate the two possible solutions: \[ x_1 = \frac{5 + \sqrt{73}}{4} \] \[ x_2 = \frac{5 - \sqrt{73}}{4} \]
Calculating \( \sqrt{73} \): \[ \sqrt{73} \approx 8.544 \]
Calculating \(x_1\): \[ x_1 = \frac{5 + 8.544}{4} \approx \frac{13.544}{4} \approx 3.386 \]
Calculating \(x_2\): \[ x_2 = \frac{5 - 8.544}{4} \approx \frac{-3.544}{4} \approx -0.886 \]
Rounding to the nearest hundredth, we get: \[ x_2 \approx -0.89 \]
Thus, the solution to the quadratic equation \(2x^2 - 5x = 6\) that rounds to the nearest hundredth is:
\(x \approx -0.89\)
Therefore, the correct response is: x = −0.89.